Chemistry matter and its changes - Brady, James E; Senese, Frederick (Hoboken, NJ Wiley, 2004)
Intended for mainstream general chemistry courses for science and engineering students, this text is comprehensive in coverage and employs devices designed to enhance the reader's critical thinking
1 13
Keywords: Chemie; Chemistry